Behavior and design implications of web-post shear failure in cellular beams - Worathep Sae-Long; Sutham Arun; Suchart Limkatanyu; Preeda Chaimahawan; Nattapong Damrongwiriyanupap; Wichaphon Fakkaew; Sangsan Wongchairattana (Results in Engineering)
Local failure is a key factor in the collapse of steel structures, particularly in beams with web openings. Cellular beams, featuring regularly spaced circular openings, are especially susceptible to multiple failure modes caused by these perforations. Among them, web-post horizontal shear failure (WPHSF) is considered one of the most critical local failure mechanisms in cellular beam design. However, research on this specific failure mode remains limited. To address this gap, this study conducts a series of parametric analyses to investigate WPHSF characteristics in cellular beams, aiming to support safer and more efficient designs. The key parameters examined are section size, opening ratio, and slenderness ratio. Steel is modeled as perfectly plastic, isotropic, and homogeneous. Numerical simulations are performed using the finite element software ABAQUS, and the results are evaluated against the ANSI/AISC 360-01 design code for predicting web-post horizontal shear capacity. The findings indicate that the ANSI/AISC 360-01 code generally overestimates horizontal shear capacity, especially for beams with larger sections or when both the opening ratio and slenderness ratio are low. In response, this study proposes an improved equation for predicting web-post horizontal shear capacity and introduces a new equation for determining the WPHSF location within the web-post of cellular beams. These results provide valuable insights for improving the design of cellular beams and mitigating WPHSF, while also clarifying the significant influence of geometric parameters on this failure mode.